Ultrasound‐Activated Precise Sono‐Immunotherapy for Breast Cancer with Reduced Pulmonary Fibrosis - Xiang Li; Gao He; Hui Jin; Xinyu Xiang; Dong Li; Renmiao Peng; Jing Tao; Xinping Li; Kaiyang Wang; Yu Luo; Xiaoan Liu (Advanced Science, 2025)
Abstract Immune checkpoint inhibitors have demonstrated remarkable efficacy across various cancer types. However, immune‐related adverse events (irAEs) pose a significant challenge in immunotherapy, particularly the associated pneumonia as the primary adverse reaction, which can lead to irreversible pulmonary fibrosis. Additionally, monotherapy with programmed death ligand (PD‐L1) inhibitors has shown limited effectiveness. Therefore, to improve the response rate of immunotherapy and reduce pulmonary fibrosis, this study designed and prepared an intelligent nanodrug based on dendritic mesoporous silica nanoparticles (DMSNs) loaded with a sono‐sensitive agent protoporphyrin IX (PpIX). Additionally, a reactive oxygen species (ROS) sensitive linker is used to attach the immunotherapeutic drug PD‐L1 inhibitor (aPD‐L1) to DMSNs via covalent bonds. The external ultrasound (US) activates PpIX to generate ROS, which breaks the linker to release aPD‐L1 to induce sonodynamic therapy (SDT) and immunotherapy. This sono‐immnotherapy approach demonstrated excellent outcomes in tumor inhibition, eliciting immune responses, and reducing pulmonary fibrosis. Overall, this study offers a new, efficient, and safe method for breast cancer treatment, and expands the application of immunotherapy.